Green Deal and financing sustainable transport in Europe: A target costing analysis - Bakkar, Yassine; Bark, Eunice; Prause, Gunnar; Ul-Durar, Shajara (Elsevier BV, 2025)
This study investigates how Europe financed an efficient and environmentally friendly transport system and supported clean shipping investments from 2012 to 2021. Grounded in target costing theory, which aims to maximize a product's future success, this paper evaluates several green European financing pools and their effectiveness in facilitating the Green Deal transformation of the transport system. Utilizing a unique dataset from the Clean Shipping Project Platform, the results of this study indicate that Europe's environmental and financial support primarily stemmed from the European Investment Bank (EIB) which began backing green investments in 2010. The findings reveal a cautious yet significant contribution of the EIB towards climate protection in the shipping industry and identify challenges in financing smaller firms and innovative technologies thus emphasizing the need for strategic fund allocation to align with the EU's climate goals. These insights have critical policy implications for EU-based financing of European environmental policies prior to the proclamation of the Green Deal, which preceded the 2021-2028 budget period, as well as for the available climate funding mechanisms aimed at achieving the COP26 targets.